State-feedback control of a rigid rotors supported on squeeze-film bearings - Akgül, H. Basri. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1988., 1988)
In this thesis, pole assignment problem, one of the most commonly used control schemes, is considered and special emphasis is given on the application of available pole assingment algorithms in multi-input systems. Various methods such as Ackermann's Procedure, ModaI ControI, Direct Design Procedure and Phase-Variable Canonical Form are explained for determining the required feedback gains for arbitrary pole assignment in single-input systems. Chapter II which includes also the methods developed for the multivariable systems. In Chapter III, the squeeze film-bearing theory is presented. Squeeze-film bearing equations, oil-film coefficients and the coordinate transformations are derived. In Chapter IV, the selected models and their characteristics are discussed. State feedback control is applied to a rotor bearing system and the computer program is developed. In Chapter V, the general conclusions of thesis are given.
Keywords: Bearings (Machinery); Control theory.; Feedback control systems.